Stable RK2-Derived Cloning Vectors for the Analysis of Gene Expression and Gene Function in Gram-Negative Bacteria - Bruno Dombrecht; Jos Vanderleyden; Jan Michiels (Molecular Plant-Microbe Interactions, 2001)
The construction of several stable RK2-derived cloning vectors for the analysis of gene expression and function in gram-negative bacteria is reported. Plasmid stability is conferred by the RK2 par locus or by insertion of the spsAB or spsCD symbiotic plasmid stability loci from pNGR234a of Rhizobium sp. NGR234. The vectors carry multiple cloning sites with protection against read-through transcriptional activity of vector sequences. Vector derivatives with the constitutive nptII promoter or a promoter-less gusA gene are suitable for the study of gene function or regulation in bacteria.